Energy efficiency improvements in longan drying practice - N. Tippayawong (2018)
This paper presents and evaluates methods of improvement of energy utilization and reduction of energy cost in conventional unpeeled longan drying. Existing dryers were modified into a new dryer arrangement. Performance in terms of specific energy utilization, thermal efficiency and operating cost indices for both traditional and new designs was evaluated. Results showed that the modified dryer yielded an average thermal efficiency of 0.35, compared to 0.29 for the existing dryer. For the same mass of dried longan produced, specific energy utilization and fuel cost were reduced by more than 16% and 80%, respectively. The improvement was attributed to fuel switching from liquefied petroleum gas to wood, heat recovery via hot air recirculation, better temperature and humidity control, and thermal insulation. The new dryer with improved design and better energy efficiency was estimated to have payback period less than 3 years. © 2008 Elsevier Ltd. All rights reserved.